Space-Based Imaging Radar Studies of U.S. Volcanoes - Dzurisin, Daniel; Lu, Zhong; Poland, Michael P.; Wicks, Charles W. (Frontiers in Earth Science, 2019)
The arrival of space-based imaging radar as a revolutionary land-surface mapping and monitoring tool little more than a quarter century ago enabled a spate of innovative volcano research worldwide. Soon after launch of European Space Agency’s ERS-1 spacecraft in 1991, the U.S. Geological Survey began SAR and InSAR studies of volcanoes in the Aleutian and Cascades arcs, in Hawai’i, and elsewhere in the western U.S. including the Yellowstone and Long Valley calderas. This paper summarizes results of that effort and presents new findings concerning: (1) prevalence of volcano deformation in the Aleutian and Cascade arcs; (2) surface-change detection and hazard assessment during eruptions at Aleutian and Hawaiian volcanoes; (3) geodetic imaging of magma storage and transport systems in Hawai’i; and (4) deformation sources and processes at the Yellowstone and Long Valley calderas. Surface deformation caused by a variety of processes is common in arc settings and could easily escape detection without systematic InSAR surveillance. Space-based SAR imaging of active lava flows and domes in remote or heavily vegetated settings, including during periods of bad weather and darkness, extends land-based monitoring capabilities and improves hazards assessments. At Kīlauea Volcano, comprehensive SAR and InSAR observations identify multiple magma storage zones beneath the summit area and along the East Rift Zone, and illuminate magma transport pathways. The same approach at Yellowstone tracks the ascent of magmatic volatiles from a mid-crustal intrusion to shallow depth and relates that process to increased hydrothermal activity at the surface. Together with recent and planned launches of highly capable imaging-radar satellites, these findings support an optimistic outlook for near-real time surveillance of volcanoes at global scale in the coming decade.